Pengaruh Modal, Promosi, Dan Lokasi Terhadap Tingkat Pendapatan Pedagang Fast Food (Studi Kasus di Geudong Kecamatan Samudera Kabupaten Aceh Utara) - Nuraida Nuraida; Suryani Suryani; Ismaulina Ismaulina (FEB Universitas Sultan Ageng Tirtayasa, 2020)
Fast food traders in Geudong are traders who come to earn income to meet the needs of their families, it's just that the income of fast food traders in Geudong must move to a new location, so there are several factors that influence it and also become the focus of this research. The purpose of this study was to determine the variables of capital, location and promotion simultaneously or partially influence the income of fast food traders in Geudong, Samudera District, North Aceh Regency. This research is a type of field research with a quantitative approach and the number of samples studied is 25 fast food traders in Geudong. This study uses a questionnaire with calculations using the likert scale. Based on the results of the study it was found that partially the capital variable gained a significant value of .002, the promotion variable had a significant value of 0,000, as well as the location variable which had a significant value of 0,002, so all the results were significant <0.05 thus this study rejected H0 and accept Ha. Then simultaneously all the independent variables namely capital, promotion, and location significantly influence the dependent variable because Fcount> Ftable (11,306> 3.05) and significant 0.000 <0.050, it can be concluded that the independent variables namely capital, promotion, and location have an effect on traders fast food in Geudong